2019
DOI: 10.1097/md.0000000000014848
|View full text |Cite
|
Sign up to set email alerts
|

Trend and survival outcome in Taiwan cervical cancer patients

Abstract: Cervical cancer is one of the most common cancers in Taiwan. The aim of this study was to estimate the incidence of cervical cancer in Taiwan, the relationship between cervical cancer and previous co-morbidities, and the long-term trend of cervical cancer mortality differences in the rest of the world.This study was based on the data of cervical cancer in the National Health Insurance Research Database from 1997 to 2013, and estimated the annual prevalence and incidence of cervical cancer. Joinpoint regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 19 publications
3
20
3
Order By: Relevance
“…The overall Pap smear rate in Taiwan is only around 50%, 64 which confers to a higher incidence of cervical cancer in Taiwan than in developed countries. 65 In our data, there is also a higher proportion of patients in advanced stages of cervical cancer than the report from Norway. 3 On the contrary, women at perinatal care may have more frequent Obstetrics clinic visits and a higher likelihood to receive Pap smear, which may confer to a better outcome in such a group.…”
Section: Discussioncontrasting
confidence: 45%
“…The overall Pap smear rate in Taiwan is only around 50%, 64 which confers to a higher incidence of cervical cancer in Taiwan than in developed countries. 65 In our data, there is also a higher proportion of patients in advanced stages of cervical cancer than the report from Norway. 3 On the contrary, women at perinatal care may have more frequent Obstetrics clinic visits and a higher likelihood to receive Pap smear, which may confer to a better outcome in such a group.…”
Section: Discussioncontrasting
confidence: 45%
“…Previous studies conducted in the United States, Vietnam, and Taiwan reported the recent peak age at 70 to 85 years, 60 to 74 years, and >85 years, respectively. [53][54][55] Differences in the peak age may affect the duration of routine screening. In the region with an older peak age, older women still may need to be screened.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, cervical cancer is preventable which is often caused by human papillomavirus (HPV) infection, particularly for two most common strains of HPV—16 and 18 [ 21 ]. HPV infection can result in precancerous lesions which increase the risk of cervical cancer [ 22 ]. Although the widespread implementation of the Papanicolaou (Pap) cytology test since the 1960s has reduced cervical cancer incidence and mortality in Canada and many high-income countries, the reductions have recently leveled off and disparities continue [ 23 ].…”
Section: Discussionmentioning
confidence: 99%